IFRS a česká účetní legislativa - Šprochová, Iveta (Vysoké učení technické v Brně. Fakulta podnikatelská, 2015)
Diplomová práce se zaměřuje na srovnání požadavků kladených na účetní výkazy sestavených podle české legislativy a podle Mezinárodních standardů účetního výkaznictví – IAS/IFRS. Předmětem práce je komparace rozdílů mezi těmito dvěma systémy na datech vybrané obchodní korporace a jejich dopad na informace ve výkazech.

The master´s thesis focuses on comparing of requirements of accounting statements which were made up according to the Czech legislation and International Financial Reporting Standards – IAS/IFRS. The main topic of the work is to compare differences between the both systems and their impact on statement information. The differences are based on the data of a selected company.
IFRS and Czech Accounting Adjustment
Keywords: Česká účetní legislativa; IAS/IFRS; Mezinárodní standardy účetního výkaznictví; účetní závěrka.; Czech accounting legislation; IAS/IFRS; International Financial Reporting Standards; financial statement.